A example of Protrepical Writing: The Euthydemus - Palpacelli, Lucia (Revista Archai, 2011)
In this paper, one of the most befuddling of Plato’s dialogues is analysed: the Euthydemus. The scene in this dialogue is dominated by two eristic speakers, word gamers, always building up sophisms, to be recognised, at the end of the discussion, as the winners. At first sight, reading this dialogue, one has the impression of facing a big word game, where words turn upon themselves, apparently concluding nothing at all. Analysing this game which characterizes Plato’s writing, it can be shown how in the Euthydemus there is much which is “not written”: there are indeed many issues which are bridges to other dialogues.